Trepidation : the internal effects of external events - Makoto, Nicholas (2019)
With worries and anxieties both past and present, Trepidation is an audio-visual glimpse into a portion of my mind; an exploration into my thoughts of the world around me and an introspective look at the often unclear roots of where my thoughts and fears come from. This essay will serve as a guide to the amalgamation that is my Final Year Project.